Germany : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
KEY ISSUES Context: ? Germany fundamentals are sound: balance sheets are generally healthy, unemployment is at a historic low, and the fiscal position is strong. ? While a recovery is underway, medium-term growth prospects are subdued and the current account surplus remains high. The economy also faces a still weak international environment, lingering uncertainty (including about future energy costs), and fast approaching adverse demographic changes. ? Germany could do more to increase its growth, thus strengthening its role as an engine of euro area recovery. Policy recommendations: ? Germany has the fiscal space to finance an increase in needed public investment, particularly in the transport infrastructure. Unlike public consumption, this would durably raise German output and have measurable growth spillovers on the rest of the euro area. ? Further reforms in services sector regulation would boost competition and productivity. ? Greater clarity about the future energy sector regulatory framework would encourage private investment in the energy infrastructure and beyond and strengthen the outlook. ? Decisions on the future level of the minimum wage should take into account the employment effects in certain regions. ? Banks should keep strengthening their capital position ahead of the completion of the ECB's Comprehensive Assessment. ? The macroprudential framework needs to be ready as monetary conditions are set to remain accommodative for a prolonged period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet